2007
DOI: 10.15376/biores.2.4.590-597
|View full text |Cite
|
Sign up to set email alerts
|

The stereochemistry and conformation of lignin as judged by X-ray crystallographic investigations of lignin model compounds: Arylglycerol beta-guaiacyl ethers

Abstract: The conformations of a variety of crystalline lignin models representing different diastereomeric forms of structural elements in lignin of the arylglycerol b-guaiacyl ether type have been studied using X-ray crystallography. Based on X-ray crystallographic data, sequences of units attached to each other by b-guaiacyl ether linkages were constructed. The appearance of the resulting oligomers shows that stereoisomerism can be expected to influence the shape of the lignin molecules to a great extent. The constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The observations that threo -diastereomers of β- O -4′ aryl ethers were preferentially degraded and incorporation of p -coumarate ( p- CA) at the γ-OH position increased resistance suggested that local steric hindrance and conformation might be major determinants for susceptibility against fungal degradation. Langer et al showed that threo -forms of β- O -4′ aryl ethers existed in a more “extended” or “open” form and, consequently, might be more accessible to or promote interaction with the diffusible oxidants . To the best of our knowledge, conformational studies on structural motifs exclusively occurring in grass lignin have not been performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations that threo -diastereomers of β- O -4′ aryl ethers were preferentially degraded and incorporation of p -coumarate ( p- CA) at the γ-OH position increased resistance suggested that local steric hindrance and conformation might be major determinants for susceptibility against fungal degradation. Langer et al showed that threo -forms of β- O -4′ aryl ethers existed in a more “extended” or “open” form and, consequently, might be more accessible to or promote interaction with the diffusible oxidants . To the best of our knowledge, conformational studies on structural motifs exclusively occurring in grass lignin have not been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Langer et al showed that threo-forms of β-O-4′ aryl ethers existed in a more "extended" or "open" form and, consequently, might be more accessible to or promote interaction with the diffusible oxidants. 84 To the best of our knowledge, conformational studies on structural motifs exclusively occurring in grass lignin have not been performed. However, steric hindrance by γ-acylating p-coumaryl groups can be easily conceived.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…42,43 To this effect, works of Langer and Lundquist have predicted substantial effects of lignin stereochemistry on structure. 44 We therefore extend the optimized, minimum-energy dimer structures in this study out to longer polymers holding the same internal bond angles, evaluating the extent to which the C-lignin polymer structure can differ on account of stereochemistry.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…44,57−60 Langer and Lundquist have suggested that the stereochemical diversity of lignin may be among the primary factors that result in complicated NMR signals, beyond the obvious heterogeneity of linkages. 44,57,61 This corresponds to the intrinsic challenge to control the chemical decomposition reactions required for efficient and economical lignin processing.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation